“PERINGATAN DARURAT” AS A CANCEL CULTURE MOVEMENT THROUGH SOCIAL MEDIA IN INDONESIA - Wempi, Jefri Audi; Chrisdina, Chrisdina; Rully, Rully (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2025)
At that time, the Indonesian government was organizing regional elections, part of the ongoing general election process following the presidential and legislative elections. In a short period, a public movement emerged to reject and cancel the Draft Law (RUU) proposed by the Indonesian Parliament, following the Constitutional Court's ruling on presidential nomination thresholds and political party participation in elections. The